Effects of Pumpkin Seed and Apricot Oil on Atherogenic Index in the Rats: an Experimental Study - Maria, Sofia Chandio, Beenish Ghafar, Nosheen Zehra Mangi, Shahida Hassan Memon, Urooj Bhatti (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the effects of pumpkin seed oil and apricot oil on the atherogenic index. Methods: This experimental study was carried out on 24 male albino rats (n=24) at the Department of Biochemistry in collaboration with the Diagnostic and Research Laboratory, Liaquat University of Medical and Health Science Jamshoro, Sindh. The study population (n=24) divided into three groups, with 8(n=8) in each group. Lipid profile determined and atherogenic index calculated by the formula log Triglycerides/HDL ratio. The atherogenic index was compared in three groups(high- fat diet group, High-fat diet+Pumpkin seed oil group and high -fat diet+apricot oil group). Data analyzed on IBM SPSS 22.0 and p value <0.05 taken as significant. Results: Serum cholesterol, triglycerides, and LDL levels were decreased in the groups of rats given high-fat diet +pumpkin seed oil group and high-fat diet +apricot oil group as compared to high fat diet controls. HDL levels increased to significant level in the groups of rats given high-fat diet +pumpkin seed oil and high-fat diet +apricot oil as compared to high-fat diet control. The atherogenic index was 1.426±0.19 in high-fat diet controls, and this decreased to 1.31 ±0.21 in the rats given high fat diet+ pumpkin seed oil and at the same time decreased to 1.20±0.14 in those given high fat diet with apricot oil. Conclusion: Pumpkin seed oil and apricot oil, both are effective in decreasing the atherogenic index in the rat taking high fat diet but apricot oil is more effective in reducing atherogenic index in the rats taking high fat diet. Keywords: Atherogenic index, Apricot oil, High fat diet, Pumpkin seed oil